German emotional concepts of safety, protection and comfort through the prism of the linguo-cultural opposition of Ordnung ‘Order’ – Chaos ‘Chaos’ - Mizin, K.; Kolesnyk, O. (Studia Philologica, 2021)
This paper considers verbal means of representing concepts of the sphere of emotions within the framework of German language worldview. The article targets conceptualized emotions connected to the notions of safety, protection and comfort. The methodology of analysis employs fundamental notions of linguo-cultural studies, cognitive linguistics and linguo-semiotics realigned along the basic point of M-logic, the theory of myth-oriented semiosis and universalia-oriented studies. Socio-cultural and enthic peculiarities of verbal representations of the emotions belonging to the "comfort quartet" are interpreted as manifestations of the system's (German "national spsirt's") compensating for the fear of the future that appears to the factor of entropy. Ethnic and linguo-cultural features of the «Sicherheit», «Geborgenheit», «Zuverlässigkeit» and «Gemütlichkeit» concepts are addressed as markers of axiological significance and further viewed through the prisom of the «Ordnung ‘Order’ – Chaos ‘Chaos’» opposition. Semantic "nano-myths" encoded in the inner form of the concepts' names are reconstructed via the etymological analysis of the units «Sicherheit», «Geborgenheit», «Zuverlässigkeit», and «Gemütlichkeit». The article discusses the transformation of primal semantic nano-myths correlated with scenarios of Germanic mythology as inchoative matrices projected onto the ethnic worldviews into secondary mythic simulacra unfolding in multiple alternative worlds in the globalized context. Correlations between the emotional phenomena and respective concepts are outlined and specified via a nultidimensional universal model that treats a human being as a biovital and biosocial open system. The highlighted tendency towards construing the said secondary mythic simulacra demonstrates the distortion in the system's (German linguoculture's, worldview's or a national semiospheric segment 's) orientation along the "Order" categorization vector. Key words: emotion, emotional concept, system, operator, semantics.